The theta system argument structure at the interface - Everaert, Martin; Marelj, Marijana, 1970-; Siloni, Tal. (Oxford : Oxford University Press, 2012)
This text considers the recent results and evaluations of the theta system in both theoretical and experimental domains. Distinguished linguists from all over the world examine the theory in the context of an array of new empirical data ranging from Germanic, Romance, and Slavic to Ugro-Finnish, and Semitic languages.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Generative grammar